Pemberian bantuan hukum oleh posbakum kepada masyarakat kurang mampu dalam perkara pidana - Nelsa Rinanda; Sumiadi S; Zul Akli (Fakultas Hukum Universitas Malikussaleh, 2021)
The Government of Aceh launched a legal aid program for underprivileged communities to protect and provide assistance to disadvantaged people in Aceh who are facing legal problems. Legal assistance for underprivileged people has been mandated by Law Number 16 of 2011, Concerning Legal Aid. Aceh Qanun Number 8 of 2017 and Governor Regulation Number 10 of 2019 are local regulations issued to strengthen efforts to provide legal assistance to underprivileged communities. But in reality, the provision of legal aid to underprivileged people at the Lhokseumawe Class 1B District Court still experiences many obstacles, especially from Posbakum as the party that has provided legal assistance, but does not get assistance fees and other constraints. The formulation of the problem in this research is what are the obstacles faced by the Legal Aid Post to provide legal assistance to underprivileged people in criminal cases at the Lhokseumawe Class 1 B District Court and what efforts are made by the Legal Aid Post when overcoming obstacles to the implementation of providing legal aid to underprivileged people in criminal cases at the Lhokseumawe Class 1B District Court. This type of research is an empirical juridical research, namely an integrative and conceptual method of analysis to identify, process and analyze documents to understand the meaning, significance, and relevance that produces descriptive data in the form of written or spoken words from the people or observed behavior. The results showed that the obstacles faced by Posbakum in providing legal assistance to the underprivileged were the delay in receiving the indictment documents submitted by the court for the Note of Defense, the lack of budget, and psychological pressure experienced by the defendant from the start of the BAP to the ongoing trial and the lack of public understanding of the existence of legal aid provided by the State. Efforts made in overcoming obstacles to the implementation of providing legal aid to the underprivileged are requesting an indictment letter from the Bhakti Keadilan Legal Institute, requesting an allocation of funds for the implementation of legal aid for underprivileged people, providing moral support to the defendant and increasing socialization efforts about assistance Law from the State to the people. It is recommended that the Regional Government and the Aceh DPR be allocated funds to Posbakum to make it more effective and efficient in providing legal assistance to underprivileged people.